Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
From the factor theorem that says, "The polynomial P(x) has x-r as a factor if and only if r is a root of the equation P(x) = 0." So if you plugged -1 into the x's in the equation and get 0 back then, x+1 is a factor. Let's do it.
[tex]( -1)^{3} -57(-1)-56=-1+57-56=0[/tex]
It works. When you plugged -1 into x, you got 0 back and that's what the factor theorem says.
Now let's test it with synthetic division. If we divide x+1 into the original equation and get a remainder of 0, then we should be good. I'll write it up on Paint and upload it.
As you can see, our remainder is 0 and our quotient is [tex] x^{2} -x-56[/tex]. This is the Factor the Polynomial part that you wanted. We can factor this into (x-8)(x+7). So our 3 roots of the equation are (x+1)(x-8)(x+7)
Hope this helps and i'm so sorry for the long reply. I forgot to put 0x^2 when I was doing synthetic division. :/ and also sorry for the unclear paint image. you can zoom in if you want. it's nothing really important it just shows me doing the synthetic division part where i divide x+1 into the original equation.
[tex]( -1)^{3} -57(-1)-56=-1+57-56=0[/tex]
It works. When you plugged -1 into x, you got 0 back and that's what the factor theorem says.
Now let's test it with synthetic division. If we divide x+1 into the original equation and get a remainder of 0, then we should be good. I'll write it up on Paint and upload it.
As you can see, our remainder is 0 and our quotient is [tex] x^{2} -x-56[/tex]. This is the Factor the Polynomial part that you wanted. We can factor this into (x-8)(x+7). So our 3 roots of the equation are (x+1)(x-8)(x+7)
Hope this helps and i'm so sorry for the long reply. I forgot to put 0x^2 when I was doing synthetic division. :/ and also sorry for the unclear paint image. you can zoom in if you want. it's nothing really important it just shows me doing the synthetic division part where i divide x+1 into the original equation.
x^3 - 57x - 56=0⇒ x(x^2-57)= 56
Verify if x= - 1 is a solution of this equation.
(-1)* [(-1)^2 - 57]=56
(-1)[1 - 57] = 56
(-1)*(-56) = 56
56 =2*28 = (-2)*(-28) = 4*14 = (- 4)*(-14) = 8*7= (-8)*(-7)
x=8 ⇒ 8*(64-57)=56 ok⇒ x=8 is a solution
x= -7 ⇒ (-7)*(49-57)=56 ok ⇒ x= - 7 is a solution
the smallest x= -7
x= - 1
the largest x= 8
Verify if x= - 1 is a solution of this equation.
(-1)* [(-1)^2 - 57]=56
(-1)[1 - 57] = 56
(-1)*(-56) = 56
56 =2*28 = (-2)*(-28) = 4*14 = (- 4)*(-14) = 8*7= (-8)*(-7)
x=8 ⇒ 8*(64-57)=56 ok⇒ x=8 is a solution
x= -7 ⇒ (-7)*(49-57)=56 ok ⇒ x= - 7 is a solution
the smallest x= -7
x= - 1
the largest x= 8
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.